Geochemistry Exploration and Geothermometry Application in the North Zone of Seulawah Agam, Aceh Besar District, Indonesia - Rinaldi Idroes; Muhammad Yusuf; Saiful Saiful; Muksin Alatas; Subhan Subhan; Andi Lala; Muslem Muslem; Rivansyah Suhendra; Ghazi Mauer Idroes; Marwan Marwan; Teuku Meurah Indra Mahlia (Energies, 2019)
A geochemistry study has been done in four geothermal manifestations—Ie-Seu’um, Ie-Brôuk, Ie-Jue and the Van-Heutz crater—located in the north zone of Seulawah Agam mountain (Aceh Besar District, Indonesia). The study was performed through water and gas analysis. Water analysis were done for all geothermal manifestations, but gas analysis was only done for the Ie-Jue manifestation that has fumaroles. Cation and anion contents were analyzed by ion chromatography, ICP-OES, alkalimetry titrations, and spectrophotometry, meanwhile isotopes were measured by a Liquid Water Isotope Analyzer. The resulting data were used for fluid and gas geothermometry calculations, and plotted in a FT-CO2 Cross-Plot and a CH4-CO2-H2S triangle diagram to obtain reservoir temperatures. The data were also plotted by a Cl-HCO3-SO4 triangle and Piper diagram to obtain the water type and dominant chemical composition, a Na-K-Mg triangle diagram to obtain fluid equilibria, the isotope ratio in the stable isotope plot to obtain the origin of water, and a N2-He-Ar triangle diagram to establish the origin of fumaroles. The water analysis results showed that (1) Ie-Seu’um has an average reservoir temperature of 241.9 ± 0.3 °C, a chloride water type, a dominant Na-K-Cl chemical composition, a mature water fluid equilibrium, and water of meteoric origin; (2) Ie-Brôuk has an average reservoir temperature of 321.95 ± 13.4 °C, a bicarbonate water type, a dominant Na-Ca-HCO3chemical composition, an immature water fluid equilibrium, and water of meteoric origin; (3) Ie-Jue has an average reservoir temperature of 472.4 ± 91.4 °C, a sulphate water type, a dominant Ca-SO4 chemical composition, an immature water fluid equilibrium and water of meteoric origin; and (4) the Van-Heutz crater has an average reservoir temperature of 439.3 ± 95.3 °C, a sulphate water type, a dominant Ca-SO4 chemical composition, an immature water fluid equilibrium and water of magmatic origin. The results of our gas analysis showed that Ie-Jue has an average reservoir temperature of 258.85 °C, and water of meteoric origin. Based on the reservoir temperatures, the geothermal manifestation of the north zone of Seulawah Agam mountain is considered as a high-temperature geothermal system suitable for power plant development.